Discrete-event simulation for outpatient flow and emergency patient arrival in a haemodialysis unit - A., Sundar; N. A. A., Rahmin; C. Y., Chen; M. A., Nazihah (Lviv Polyteching National University, 2023)
Emergency cases among dialysis patients are uncertain and if these patients failed to obtain treatment within allocated treatment, it might risk their health conditions. In relation to that, we would like to accommodate outpatients together with the emergency patients in patient scheduling problem. Discrete-event simulation is used to estimate the outpatients flow based on the mean arrival rate, ». A modified integer linear programming model is presented in this paper which highlighted on the patients arrival time, patients departure time and bed availability for emergency case. A rescheduling algorithm is also presented to accommodate existing outpatients and emergency patients. The results show that by rescheduling the existing outpatients and emergency patients in the system, there is no delaying for the outpatients dialysis treatment. Hence, the emergency patients are able to accommodate in the system.